Oscillations in solar-type stars tidally induced by orbiting planets - Terquem, C; Papaloizou, J; Nelson, R; Lin, D (1997)
We examine the effect of dynamical tides raised by a companion on a solar-type star. In these binaries, gravity or g mode oscillations are excited by the companion in the radiative region beneath the convective envelope of the star. They become evanescent in the convection zone. This is of particular interest in connection with the newly discovered planets, some of which are found to orbit around solar-type stars with a period comparable to that of the high order g modes of the star. One such example is 51 Pegasi. Here, we determine the magnitude of the perturbed velocity induced by the tides at the stellar surface. We show that, in the case of 51 Pegasi, this velocity is too small to be observed. This result is insensitive to the magnitude of the stellar turbulent viscosity assumed and is not affected by the possibility of resonance, which occurs when the frequency of the tidal disturbance is close to that of some normal mode of the star. We also discuss the orbital evolution and synchronization timescales associated with the tidal interaction.